Perceptions of grade one pupils on video games installed in hand-held devices - Daelo, Sarah Mensie L. (College of Education, University of the Philippines Diliman, 2020)
This research employed a multiple case study design to describe the perceptions of the grade one pupils on video games installed in hand-held devices in terms of purpose, preference and content. With a sample of five first graders from selected private schools in Lucena City, qualitative data analysis was done using the following: interview guide for the student and parent participants and observation grid for the first graders. The results showed that student participants perceptions were influenced by their experience, socio-cultural background and physical and emotional development. Video games are played mainly for the purpose of entertainment regardless of different technology exposure in school and at home. The installed video games in the hand-held devices of the first graders have different themes such as biblical, strategic ball games, accomplishing tasks, puzzles and mazes, dressing-up, sports, racing, and violence. Female participants were more into task-oriented games and fashion while male student participants were more into games that content building, racing and violence. There were no sexual content nor harmful words found among the video games. Most of the participants enjoyed playing video games that involve progression by accomplishing a stage before proceeding to the next level. Recommendations for various stakeholders and proposals for further studies are included in this research.